1998
DOI: 10.1089/hyb.1998.17.133
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human IgG1 Monoclonal Antibody Against Gangliosides Expressed on Tumor Cells

Abstract: A human IgG1.k monoclonal antibody (MAb) designated GMA1 was developed by fusing pooled lymph node lymphocytes from cancer patients with the human lymphoblastoid cell line, SHFP-1. The GMA1 MAb reacted with several melanoma and neuroblastoma cell lines. Normal tissue derived from human brain and tumor-cell lines derived from colon, ovary, and breast were not reactive. FACS analysis performed using live cells demonstrated that the antibody recognizes a cell-surface antigen. Enzyme immunoassay (EIA) and thin lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Silent auto-reactive B clones have also been identified in cancer patients, from which human monoclonal antibodies (mAb) against gangliosides were generated. The mAb GMA1 reacted with the gangliosides GD3, GM3, and GD2 from melanoma and neuroblastoma cell lines and not normal tissues (Mukerjee et al, 1998). The human monoclonal IgM antibody 7c11.e8, also generated by fusing lymph node cells isolated from a surgical specimen of malignant melanoma reacted with GM4, GM3, and GD3.…”
Section: Naturally Occurring Anti-ganglioside Antibodiesmentioning
confidence: 99%
“…Silent auto-reactive B clones have also been identified in cancer patients, from which human monoclonal antibodies (mAb) against gangliosides were generated. The mAb GMA1 reacted with the gangliosides GD3, GM3, and GD2 from melanoma and neuroblastoma cell lines and not normal tissues (Mukerjee et al, 1998). The human monoclonal IgM antibody 7c11.e8, also generated by fusing lymph node cells isolated from a surgical specimen of malignant melanoma reacted with GM4, GM3, and GD3.…”
Section: Naturally Occurring Anti-ganglioside Antibodiesmentioning
confidence: 99%
“…These IgM antibodies also exhibited characteristics common to conventional antisera, like cross-reactivity or poly-specificity and low affinity. The antibodies also reacted not only with membrane-bound structures, but also with cytoplasmic and nuclear proteins, and with carbohydrate structures and glycolipids [31][32][33][34][35][36]. Subsequent sequence analysis revealed that these human IgM antibodies with anti-tumour activity were part of the innate (natural) immunity, germ-line coded and not affinity maturated [37][38][39].…”
Section: The Igm Traumamentioning
confidence: 99%
“…One will consist of known antigens such as the Ep-CAM antigen [23], the antigen to AE6F4 [20], or the ganglioside GD3 [24,25], and the other class will consist of novel antigens such as AgSK1 [18] or AgTB94 [21,22], which have not been previously described. This could be significant, especially in light of the fact that the human immune response recognises allotypic antigens immunologically blind to other species.…”
Section: Glassy Yasutomi and Koda 997mentioning
confidence: 99%
“…Prior studies [7,14,18,19,24,31] have demonstrated the clinical utility of obtaining antibody-secreting B-cells from regional draining lymph nodes and their applications in cancer diagnosis and therapy. The principles learned should be applicable to lung cancer.…”
Section: Experimental Modelmentioning
confidence: 99%
See 1 more Smart Citation